2020
DOI: 10.1016/j.ejvs.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Durability of Open Repair of Juxtarenal Abdominal Aortic Aneurysms: A Multicentre Retrospective Study in Five French Academic Centres

Abstract: WHAT THIS PAPER ADDS This multicentre study suggests that in fit patients, open juxtarenal abdominal aneurysm repair can be performed with acceptable operative risk and with durable results in terms of both graft integrity and preservation of renal function. Predictors of acute kidney injury (AKI) were pre-existing chronic kidney disease, diabetes, hypertension, and age. The level and duration of renal artery clamping (24 AE 7 min, range 10e55 min) were not associated with an increased risk of AKI in this grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
1
12
0
5
Order By: Relevance
“…Aortic aneurysm is the damage to the normal structure of the aortic wall caused by various reasons. Under blood flow pressure, the aortic wall locally or diffusely expands abnormally to more than 1.5 times the normal aortic diameter [ 1 ]. It often occurs in the ascending aorta, aortic arch, descending thoracic aorta, thoracic abdominal aorta, and abdominal aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic aneurysm is the damage to the normal structure of the aortic wall caused by various reasons. Under blood flow pressure, the aortic wall locally or diffusely expands abnormally to more than 1.5 times the normal aortic diameter [ 1 ]. It often occurs in the ascending aorta, aortic arch, descending thoracic aorta, thoracic abdominal aorta, and abdominal aorta.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Chong et al 7) reported that the patients who required SR cross-clamping during open AAA repair had an operative mortality rate of 1.8%, which was similar to the rate of 1.1% that they observed after IR AAA repairs. More recently, Chaufour et al 8) reported that the operative mortality rate following open juxtarenal AAA repair in French high-volume centers was 0.9%.…”
Section: Discussionmentioning
confidence: 99%
“…In einem italienischen Zentrum machte die 30-Tage-Letalität bei OAR von 155 juxtarenalen AAA sogar nur 0,6 % aus, die postoperative Morbidität 10 % [6]. Fünf akademische Zentren aus Frankreich berichteten über eine multizentrische konsekutive Serie von 315 OAR juxtarenaler AAA [3]. In dieser Serie wurden lediglich 3 (0,9 %) Todesfälle postoperativ (30-Tage-Letalität und Klinikletalität eingeschlossen) gesehen, postoperative Komplikationen traten in 14,6 % auf.…”
Section: Diskussionunclassified